The Phenomenon of Digital Media Consumption: An Overview of Pornography Access via Social Media among Students of the Faculty of Health Sciences - Rahwani Majid; Sitti Nurhidayanti Ishak; Norma B. Toduho (BIOSAINSTEK, 2026)
The phenomenon of pornography in Indonesia is no longer a minor issue. At present, pornography has become very alarming. Pornography is a problem that has not yet been resolved, and it continues to grow rapidly without any decline, despite the many dangers associated with consuming pornography. The purpose of this study is to examine the use of social media and access to pornography among students at the Faculty of Health Sciences in 2025. This research is quantitative in nature with a cross-sectional study design. It was conducted at the Faculty of Health Sciences, UMMU, in 2025. The research was conducted in January 2025. There were 57 respondents, and the sampling technique used was accidental sampling. Data collection instruments used questionnaires, which were analyzed using descriptive univariate analysis. The results showed that the majority of respondents stated that they were addicted to social media, with 35 people (61.4%). Meanwhile, 29 respondents (50.9%) used social media for 3-5 hours per day. This shows that more than half of the respondents had a fairly high intensity of social media use every day. Instagram was the most widely used social media platform among respondents, with 34 people (59.6%). Meanwhile, there were 8 respondents (14.0%) who admitted to having deliberately searched for pornographic content. Although the number is not dominant, this figure still shows that a small number of respondents consciously accessed such content.